Renewable energy resources in Hungary – solid biomass utilization in terms of necessity and opportunity - Erős , Veronika; Biró, Tamás (Applied Studies in Agribusiness and Commerce, 2010)
In the 21st century a country’s success significantly depends on how it can solve the problems (supply safety, growing prices, climate change, etc.) induced by the application structure of the fossil energy sources with the means of energy saving, energy efficiency and the utilization of renewable energy resources. The utilization of renewable energy sources has positive effects on five key areas: environment protection, energy policies, fulfilment of EU expectations, agriculture and rural development and on the whole of the national economy. The bioenergy – beside fulfilling the national economic aims – it is putting up the value of the role of agriculture and rural development. The role of agriculture is multi-functional in the process. The agricultural sector has an important task in the area of bioenergy to ensure the proper quality and quantity of raw materials for the increase of bioenergy utilization. This also means new sales perspectives and opportunities for the producers. Above all this, the agricultural policy aims for the agriculture and the rural development segment to be the unambiguous winner of the new bioenergy sector and for most of the available profit to stay with the agricultural sector, with the rural players. For this reason encouraging the raw material production it wishes to encourage the producer their primary process and their local utilization. One of the fundamental objectives of the measures is that agriculture should go beyond the raw material production and take steps towards processing and utilization. The multifunctional role in the product chain might mean extra income and more added value for the producers and the active players in the process. The other objective is to promote the local utilization, the scatter of the environmentally friendly energy sources in rural areas, to change the energy is “lying on the ground unutilized” principle while local processing and promoting the utilization, to achieve a lower energy dependency and to optimize and disseminate cost efficient solutions. To realize all this means a great task and a huge challenge for the agricultural government as well as the rural societies and micro regions but might lead to a successful rural development. The range of the tools and measures to fulfil the aims might be very broad, from the regulating instruments to the various subsidies, coordination and dissemination tools. Part of the subsidy schemes are direct production-type of subsidies (the so called direct payments, for example the area based subsidies) and the other main forms are the investment-type subsidies which are for technology development, promotion of competitive production and local processing and for establishing a green energy industry. In the period of 2007-2013 the key elements of the development schemes were drafted in the frame of the New Hungary Rural Development Programme (ÚMVP) and the Environmental Energy Operational Program (KEOP). The available raw materials and the conditions are taken into consideration while designing the development schemes because a successful realization of a product chain means the assurance of the inputs and outputs. The starting point of determining the development direction is the principle of an operation which is sustainable and economical on the long run. In addition such developments are considered reasonable which are viable on medium and long term and bring numerous rural development, environmental and societal returns.